Cataclasis and plastic deformation of quartz at the epithermal silver occurrence Aid (Taryn subvolcanic massif, Eastern Yakutia) - O. A. Sustavov (Литосфера, 2015)
On the silver occurrence Aid in Taryn subvolcanic massif a comb vein quartz is in some places exposed to cataclasis and plastic deformation. There are the cataclastic flow of quartz with the fragmentation of crystals, by shear microfractures and the formation of cataclasis zones in which the fragments of quartz with size of parts of a millimeter cemented by cryptograined quartz matrix. Inside and around some cataclasis zones a comb quartz plastically deformed to form the subprismatic and subrhombohedral deformation bands, deformation lamellae and “spotted” undulatory extinction, like a kind of arising in the experimental deformation of quartz at low temperatures, high stress and high strain rates. To the places of occurence in the cataclasis zones walls of the systems of subordinated microshears timed the “lenticular” quartz (first described) consisting of the plastically deformed lenticular fragments of the original quartz, in which the c axis with respect to the matrix reoriented to an angle of 90°. Cataclasis and plastic deformation of quartz placed together, which may be due to a combination during faulting in epithermal environment the favoring cataclasis low confining pressure and the enough high temperature for plastic deformation of quartz.